Crime, Inequality, and the Private Provision of Security - Jan Heufer (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2011)
In a high-crime environment with many high-income citizens, private security companies which offer protection against crime can flourish. In this article crime is modelled as a game where richer victims yield a higher return on crime, but with decreasing returns to crime as more criminals choose crime to supplement their income. Private security providers offer protection against crime and face Cournot competition. The model allows for the analysis of market clearing prices for effort against crime. Among the implications of the model are that rising inequality will lead to more expenditure on protection against crime, and that the upper income classes are suffering from the same or lower crime density than the middle income class. Taking into account the response of criminals and victims, rising inequality can actually lead to less crime if either (i) the legal income opportunity of the marginal criminal increases or (ii) marginal utility from income decreases and richer individuals spend a higher proportion of their income on protection (i.e. protection is a superior good). Often the middle class suffers from higher crime densities as inequality increases, as the increased spending on protection by the upper class (i) shifts crime to the middle class and (ii) increases market prices for protection, leaving the middle class with less affordable protection against crime. Emigration of the middle class can then further increase inequality. This highlights the importance of taking into account the response of individuals against crime and shows that the link between inequality and crime is a complex one. – – In diesem Artikel wird Kriminalität als Spiel modelliert, in welchem wohlhabenere Opfer mehr Gewinn erbringen; dieser Gewinn nimmt aber ab, je mehr Kriminelle sich auf wohlhabene Opfer konzentrieren. Private Sicherheitsdienstleister bieten Schutz gegen Kriminalität an und stehen im Cournot-Wettbewerb miteinander. Das Modell erlaubt die Untersuchung markträumender Preise für Sicherheitsdienstleistungen. Das Modell impliziert unter anderem, dass steigende Ungleichheit der Einkommensverteilung zu höheren Ausgaben für Sicherheitsdienstleistungen führt, und dass die oberen Einkommensschichten unter dem gleichen oder sogar geringeren Maß an Kriminalität leiden als mittlere Einkommensschichten. Es zeigt sich, dass steigende Ungleichheit Kriminalität sogar reduzieren kann, wenn (i) legale Einkommensmöglichkeiten des marginalen Kriminellen steigen und/oder (ii) der Grenznutzen des Einkommens abnimmt und wohlhabendere Individuen einen höheren Anteil ihres Einkommens für (superiore) Sicherheitsdienstleistungen ausgeben. Mittlere Einkommensschichten können bei steigender Ungleichheit unter mehr Kriminalität leiden, da steigende Ausgaben für Sicherheit durch höhere Einkommensschichten (i) Kriminalität auf niedrigere Einkommensschichten verlagern und (ii) den Marktpreis für Sicherheitsdienstleistungen erhöhen. Emigration der mittleren Einkommensschichten kann dann zu einem weiteren Anstieg der Ungleichheit führen.
Keywords: D10; D30; D40; K42; 330; Crime; inequality; competition of security companies; private enforcement of law; private provision of security